Building adaptive capacity and improving food security in semi-arid Eastern Kenya - Recha, John W.M.; Radeny, Maren A.O.; Kimeli, Philip; Atakos, Vivian; Kisilu, Rachel; Kinywee, Julius (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
Collective action has led to increased agricultural investments, and provided an avenue for dissemination of climate-smart technologies. Cereal–legume intercrop innovations offer farmers multiple benefits that contribute to increased farm resilience, greater food security and better incomes. Farmers are taking up soil and water management practices to address the risk of declining rainfall amounts and variability. Wote in semi-arid zone of eastern Kenya, is characterized by highly weathered soils. Soil erosion is rampant due to lack of adequate vegetation cover at the beginning of the rainy seasons, and also due to the sparse shrubs. Land degradation and limited soil fertility replenishment have contributed to reduction in agricultural productivity, reducing potential crop yields due to soil nutrient depletion. The population density is estimated at 110 persons per square kilometre.